Cause of Death: Lähiö: Stereotypes, Utopias and Dystopias in Turku City Theatre’s - Lindroos, Sanni (Nordic Theatre Studies, 2023)
As geographically and socially marginalized neighbourhoods, Finnish lähiös are associated with urban segregation and a set of stereotypes about their residents. Claiming to portray everyday life in the lähiö, in 2018, Turku City Theatre premiered a musical theatre production Varissuo, which was set in the city’s largest and most multicultural housing unit. This article investigates how Varissuo was constructed and depicted both on stage and beyond the stage by analyzing several characters and their storylines, as well as material details present in the theatre building’s lobby area. Drawing from Richard Dyer’s notion of stereotypes as a product of assumed consensuses about specific social groups, the article first focuses on plotting how both novelistic and stereotypical characters contributed to an understanding of the lähiö as a locus of ill-being and personal struggle. Critically approaching Jill Dolan’s conceptual utopian performatives, the article then discusses the elements of utopia and dystopia in Varissuo, suggesting that the representation of the lähiö on stage and in the theatre building erased political potential of the utopian performatives and subverted them into a counterproductive force. I argue that the utilization of lähiö stereotypes and Varissuo’s detachment from its real-life origins potentially contributes to further stigmatization and polarization between social groups